Variants in relation to clinical manifestation of rabies in dogs - A. Shruthi (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 2021)
Rabies is one among the most dangerous diseases reported to have a wider range of incubation period and clinical signs. The disease is manifested as furious or paralytic forms in dogs. The combined effects of virulence and pathogenicity of the virus along with host immune factors are the main variables leading to variation in manifestation of the disease. This paper reports the finding of a study conducted in rabies positive canine cases to correlate the role of pathophysiological factors in clinical manifestation of rabies. A total of 23 rabies positive cases were studied and their anamnesis collected. Male dogs less than 5 years of age constituted major proportion of rabies positive cases. Site of bite was observed as a critical factor in disease manifestation. Anti-rabies prophylactic vaccination had significant effect as none of the vaccinated animals developed furious form of rabies. But paralytic form was found in irregularly vaccinated dogs, probably due to effect of vaccination imparting partial immune response in these animals.